Production of value-added meat patties by addition of pomegranate (Punica granatum) and Lemon (Citrus limon) extracts - Algarni, Eman (Italian Journal of Food Science, 2025)
This study investigates the enhancement of quality and shelf stability in meat patties made from spent hen meat through the incorporation of natural extracts from pomegranate (Punica granatum) and lemon (Citrus limon). In response to growing consumer demand for natural ingredients, the research focuses on spoilage, texture, and flavor in meat products. Spent hen meat was selected due to its availability and potential for value addition. Meat cubes were treated with varying concentrations of the extracts and stored under refrigeration to facilitate the absorption of bioactive compounds. Results indicated that pomegranate and lemon extracts significantly improved sensory attributes, including flavor, tenderness, and juiciness, making the patties more appealing. Notably, pome-granate extracts reduced cooking loss, suggesting better moisture retention, whereas higher concentrations of lemon extract were associated with increased cooking loss. Both extracts demonstrated antimicrobial properties, potentially extending shelf life and enhancing nutritional profiles. This study underscores the potential of these extracts to improve the overall quality and safety of spent hen meat patties, aligning with consumer preferences for healthier, natural options. Future research should focus on identifying optimal extract concentrations to maxi-mize benefits and ensure consumer acceptance.